2021
DOI: 10.1186/s13550-021-00759-w
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative [18F]FDG flexible autoradiography for tumour margin assessment in breast-conserving surgery: a first-in-human multicentre feasibility study

Abstract: Introduction In women undergoing breast-conserving surgery (BCS), 20–25% require a re-operation as a result of incomplete tumour resection. An intra-operative technique to assess tumour margins accurately would be a major advantage. A novel method for intraoperative margin assessment was developed by applying a thin flexible scintillating film to specimens—flexible autoradiography (FAR) imaging. A single-arm, multi-centre study was conducted to evaluate the feasibility of intraoperative [18F]FD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Out of the positive findings, we saw that state-of-the-art research in the related field proved that such detectors carry a sensitivity suitable for clinical translation [67]. Other research group demonstrated that the imaging skins could improve spatial resolution compared to a flat scintillator when conforming to the geometry of the specimen [46,52].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Out of the positive findings, we saw that state-of-the-art research in the related field proved that such detectors carry a sensitivity suitable for clinical translation [67]. Other research group demonstrated that the imaging skins could improve spatial resolution compared to a flat scintillator when conforming to the geometry of the specimen [46,52].…”
Section: Discussionmentioning
confidence: 98%
“…Though they did not disclose the specifications of their material, they were able to detect activity at 0.9 kBq ml −1 for 18 F using a 6 µm flexible scintillator. In [67], a 12 µm thick version of the scintillator was used to detect tumour margins in breast-conservation surgery (BCS). They successfully proved that their technique was efficient for the intraoperative assessment of excised surgical specimens.…”
Section: State-of-the Art In Stretchable Scintillatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, radio-frequency spectroscopy (MarginProbe® device [22,23]) and bioimpedance spectroscopy (ClearEdge™ device [24]) have been shown to be useful for real-time intraoperative assessment of the surgical margins in BCS in clinical trials. In addition, [ 18 F] FDG flexible autoradiography (FAR) imaging with the LightPath® Imaging System was evaluated in its feasibility of intraoperative assessment of the surgical margins in BCS in the multi-centre study [25]. These modalities, however, have disadvantage in their inability to assess the cancer cell morphology unlike the CTS assay.…”
Section: Discussionmentioning
confidence: 99%
“…Other intraoperative CLI include the use of 2-[ 18 F]FDG for the identification of surgical margins in breast conserving surgery. From published studies, there is evidence that a pre-operative administration of about 300 MBq of 2-[ 18 F]FDG would deliver maximal personal equivalent doses of 34.0 -61.8 µSv (14,29). Interestingly, if the Fluorine-18 decay characteristics and assuming an administration of 300 MBq are substituted in our model, we obtain exposure levels of 51.3, 15.3 and 4.6 µSv per procedure for the first surgical assistant, scrub nurse and robotic surgeon, respectively.…”
Section: Discussionmentioning
confidence: 99%